THE INFLUENCE OF INVESTMENT INTERMEDIARIES ON THE CORPORATE SECTOR DEVELOPMENT OF UKRAINE - Zhylinska, Oksana; Bazhenova, Olena; Bukalo, Anna (Ekonomika, 2012)
As the world experience shows, countries with the developed market economy are characterized by a high level of investment intermediation, as well as by an effective cooperation and interdependence of investors and corporations. The practice of domestic corporations shows also the objective dependence of the development level of intermediation and corporate sector that is stipulated. So in this study, the impact of investment intermediaries on the corporate sector development was estimated on the basis of econometric modeling. The result of the research is a proof of investment intermediaries operation in the domestic corporate sector that generally requires finding the way to increase the impact of their activities on the development level of the corporate sector. Investment intermediators’ activation opportunities as to corporate sector investments with some challenges are shown in their investments into the Ukrainian corporate sector.